Relations between incomes and expenditures on food of Polish households: Regional perspective - Małgorzata Leszczyńska (Economic and Environmental Studies (E&ES), 2019)
The article assesses the economic condition of households in a time frame view (2000-2016) in the light of income and expenditure (including food expenditure) on an all-Poland scale. It compares selected relations of these categories and indicates the economic health of the households in different regions of Poland. It has been assumed, as a point of reference, that polarisation of the analysed variables is dependent on the geographical area of residence. The data from the research on household budgets performed by GUS was used. A comparative analysis shows that despite the significant improvement in the financial status of households, there are still serious regional disparities. Especially The Eastern region is adversely marked in this respect.
Keywords: D14; D31; R2; 330; income; expenditures; expendiure on food and bevarages; prosperity; household; regional analysis